Media, culture and society in Iran : living with globalization and the Islamic state - Semati, Mehdi (Iranian studies (London, England), 2008)
Arguing that existing perspectives on contemporary Iran have not fully grasped the significant role of culture in Iran, this book examines modern culture and media in Iran through a wide range of topics.